Political Challenges Facing Religious Tourism and Pilgrimage Routes: Analytical Study of Lalibela, one of Ethiopia’s most Sacred Locations - Muhammad Umar Riaz Abbasi; Dr. Hafiz Muhammad Idrees; Rabia Aamir (Al-Qanṭara, 2022)
Abstract Scholars and organizations around the world are increasingly acknowledging the importance of tourism in general and religious tourism in particular. Several countries are considering religious tourism as a viable development strategy for rural and secluded religious locations. There is still a lack of research and identification of religious tourism in Ethiopia as a viable development option Lalibela, one of Ethiopia's most sacred locations, has a lot of untapped potential and present challenges that need to be examined in this study. Study results show this site is Ethiopia's most spectacular religious tourism destination, thanks to its rich religious legacy, including centuries-old annual religious festivals and multiple living rock-hewn churches with a vibrant local cultural scene. In addition to the town's religious atmosphere, the residents are quite welcoming. Poor infrastructure, harassment, beggarly behavior, trafficking in cultural property, lack of community involvement, social deprivation, and an absence of government interest to the region are just a few of the challenges facing the study area's religious tourism industry. Consequently, more productive and corrective steps are needed from all tourist stakeholders to eliminate growth impediments and to expand the area's potential.